Pola Pendampingan Oran Tua dalam Proses Belajar Anak Di TK Negeri Pembina Kota Gorontalo - Nurlita, Nurlita; Arsyad, Lukman; Utina, Sitriah Salim (Jurnal Euforia, 2025)
Early childhood education (ECED) is a level of education for children under the age of seven to prepare them for primary education. In the process, parents play an important role in supporting children's learning. In TK Negeri Pembina Gorontalo City, parental involvement is an issue that needs to be studied because it can affect children's independence. This study aims to analyze the patterns and limits of parental assistance in children's learning process. This research uses a descriptive qualitative approach with observation, interview and documentation methods for six informants. The results show that parental assistance at home has a positive impact on children's independence, while assistance in the classroom actually hinders their social interaction and independent ability. School policies that limit parents' presence in the classroom aim to encourage children to be more independent, although temporary assistance is still needed for children with special needs. A balanced pattern of assistance between home and school is very important in the development of children. In addition, time and place limits on parental assistance play a role in shaping children's independence and social skills, so that they can be more confident in exploring their own abilities.